PEDAGOGICAL FACTORS OF ORGANIZATION OF INDEPENDENT STUDENTS IN MODERN CONDITIONS - Abdumannon Abdullaevich Umarov; Umarova Ra’no Xamraqulova; Axrorova Feruza Abduvohid qizi (Scholar Express Journal, 2021)
This article describes the organization of independent learning of students in modern conditions, the essence, main goals and objectives of independent work of students, its need to improve the quality of the educational process, the types of independent learning. The types of independent work performed in the classroom and outside the classroom, the role of the electronic complex created in the subject in improving the efficiency of students' independent work are highlighted.
Keywords: educational technologies; independent education; pedagogical consultant; expert